Electrochemical performance of hybrid supercapacitor device based on birnessite-type manganese oxide decorated on uncapped carbon nanotubes and porous activated carbon nanostructures. (1st November 2018) - Ochai-Ejeh, F.; Madito, M.J.; Makgopa, K.; Rantho, M.N.; Olaniyan, O.; Manyala, N.
Abstract: Birnessite-type MnO2 synthesized on the surface of carbon nanotubes (CNTs) via facile hydrothermal reflux technique to produce MnO2 -CNT nanocomposite and 3D microporous nanostructured activated carbon (AC) derived from cork (Quercus Suber) with good microstructural, morphological and electrochemical properties are herein reported. A hybrid supercapacitor device comprising of MnO2 -CNT nanocomposite as positive electrode and AC as the negative electrode was successfully fabricated and tested for energy storage application. The device displayed a maximum working potential of up to 2 V due to the excellent synergistic contribution from the MnO2 -CNT nanocomposite and AC material derived from cork (Quercus Suber). The fabricated device displayed good electrochemical performance having an energy density of ∼25 Wh Kg −1 that corresponds to a power density of 500 W Kg −1 at a current density of 0.5 A g −1 in a 1 M Li2 SO4 aqueous neutral electrolyte. The device exhibited an excellent stability of ∼100% coulombic efficiency after 10, 000 charge-discharge cycles and excellent capacitance retention after potentiostatic floating test for 60 h. Graphical abstract: Highlights: Birnessite-type manganese oxide decorated on uncapped carbon nanotubes was synthesized via facile. Activated carbon (AC) was derived from a cork (Quercus Suber). A hybrid device was successfully fabricated using MnO2 -CNT as the positive electrode and AC as negative electrode. The electrode materials exhibited good electrochemical performance.